A Primer of Freudian Psychology - Hall, Calvin S. (New York Meridian Books, 1999)
Culled from forty years of writing by the founder of psychoanalysis, A Primer Of Freudian Psychology introduces Freud's theories on the dynamics and development of the human mind. Hall also provides a brief biography of Sigmund Freud and examines how he arrived at his groundbreaking conclusions. In discussing the elements that form personality, the author explains the pioneer thinker's ideas on defense mechanisms, the channeling of instinctual drives, and the role of sex in male and female maturation. Lucid, illuminating, and instructive, this is an important book for all who seek to understand human behavior, in themselves and others.